Potential use of denitrifying bacteria in reduction of nitrogenous compounds in the effluent discharged into lake Victoria, Kenya - Wachira, J.M. (University of Embu, 2022)
Nutrient loading with nitrogen and phosphorus in receiving waters is an increasing concern worldwide. In Lake Victoria basin, the substantial inflow of nutrients has led to intensive eutrophication of the lake. This has negatively affected not only the economic but also aesthetic as well as ecological functions. Nitrogen cycle in the atmosphere is driven by symbiotic and free-living microorganisms, which reduces dinitrogen gas to bioavailable ammonia. Ammonia is oxidized completely by a two-step aerobic pathway (nitrite-nitrate) while denitrifiers close the cycle by reducing nitrate to dinitrogen gas. Bioremediation of contaminated water using microbes has demonstrated to be a promising technology for future development because it’s not only eco-friendly but also cost-effective. In this study, we explored the diversity of bacteria involved in nitrogen cycling and their bioremediation potential within Lake Victoria. Samples were collected using sterile bottles and immediately transported to SGS Kenya Limited Laboratory Services for the physiochemical parameters analysis. Others were taken to University of Embu laboratory for further analysis. Total prokaryotic diversity in the collected samples were assessed using universal primers followed by Illumina sequencing. A culture dependent approach was used to recover aerobic denitrifiers using a medium with (NH4)2SO4 as the main N source and Bromothymol blue medium (BTB). Serial dilution was done and spread plated onto the BTB media followed by incubation. Single colonies were picked from the plates and sub-cultured in the same media to obtain pure isolates. Pure cultures obtained were presumptively characterized based molecular tests. Molecular characterization was achieved by extracting the DNA of each isolate, amplifying 16S rRNA gene using universal primers, and sequencing. Screening for Nitrogen removal was done by growing the known isolates in LB medium, harvesting by centrifugation and the obtained pellets spread plated onto screening medium containing (NH4)2SO4 as the main N source. N removal from effluent samples was analyzed by inoculating a single colony into 50 ml of sterilized wastewater. Sequences were edited using Chromas Lite and compared to those sequences in the public data bases via Basic Local Alignment Search Tool in the National Centre for Biotechnology Information. The phylogenetic analyses was done using Molecular Evolutionary Genetics Analysis MEGA X using the neighbor-joining method. Taxonomic distribution and the chemical data was analysed using QIIME2. The data generated will therefore offer a new perception on the potential use of pure cultures in treating nitrogen-rich wastewater.